Designing an Accounting Recording System Using the Microsoft Access Application at the Center Laundry - Hendi Hendi; She Lee Susanti (Universitas Internasional Batam, 2023)
Center Laundry uses manual records and has never used a systematic accounting recording system to record every transaction. Manual recording carried out by the Center Laundry makes it difficult for the owner to be aware of his financial condition because of the lack of accuracy in using manual records. Therefore, a solution for Center Laundry is to make an accounting recording system through Microsoft Access. The purpose is to assist the owner in running and managing finances. The target of these practical activities is to assist the Center Laundry in designing a financial recording system to make it easier for the owner to monitor the company's finances and be the owner in making decisions. This system will provide recording forms for cash disbursement transactions, purchases, sales, and record inventory. The result of the implementation of this PKM project is to produce complete and accurate financial reports consisting of profit and loss, purchase, sales, remaining inventory, statement of financial position, statement of changes in equity as well as trial balance Center Laundry uses manual records and has never used a systematic accounting recording system to record every transaction. Manual recording carried out by the Center Laundry makes it difficult for the owner to be aware of his financial condition because of the lack of accuracy in using manual records. Therefore, a solution for Center Laundry is to make an accounting recording system through Microsoft Access. The purpose is to assist the owner in running and managing finances. The target of these practical activities is to assist the Center Laundry in designing a financial recording system to make it easier for the owner to monitor the company's finances and be the owner in making decisions. This system will provide recording forms for cash disbursement transactions, purchases, sales, and record inventory. The result of the implementation of this PKM project is to produce complete and accurate financial reports consisting of profit and loss, purchase, sales, remaining inventory, statement of financial position, statement of changes in equity as well as trial balance